Impact of Interest Rate Deregulation on Investment Growth in Nigeria - Obinna, Osuji (International Journal of Economics and Financial Issues, 2020)
The study examined the impact of interest rate liberalization on investment in Nigeria from 1961 to 2017 using error correction model (ECM) and variance decomposition of vector autoregressive model. The empirical findings of the study showed that interest rate liberalization has no significant impact on investment in Nigeria. The result further showed that prime lending rate had a negative insignificant impact on investment in Nigeria both in the pre and post liberalization period. Private sector credit and Nominal exchange rate were also observed to be insignificant factors explaining variations in investment in Nigeria. However, national income and government expenditure exerted a positive and negative significant impact on investment respectively. The study therefore recommended that government through the Central Bank of Nigeria should use her monetary policies to influence interest rate in such a way as to stimulate investment growth in the country instead of allowing it to be freely determined by the market forces as the theory on liberalization suggests. Keywords: Interest rate, Investment, Nigeria JEL Classifications: E43, E22 DOI: https://doi.org/10.32479/ijefi.9260